All-cause excess mortality associated with the Lāhainā, Maui fires - Nakatsuka, Michelle; Taparra, Kekoa; Renton, Benjamin; Chen, Alexander Junxiang; Chen, Ji; Krumholz, Harlan M.; Faust, Jeremy Samuel (Frontiers in Climate, 2025)
ObjectivesTo quantify all-cause excess mortality, defined as the number of deaths exceeding the expected baseline, associated with the 2023 Lāhainā wildfire in Maui County, Hawai‘i, and highlight public health implications.MethodsExcess mortality was estimated using seasonal autoregressive integrated moving average models trained on data from August 2018–July 2023. Projections were generated via 5,000 bootstrapped simulations, with a sensitivity analysis excluding COVID-19-attributed deaths.ResultsAugust 2023 reported 82 (95% CI: 55–100) excess deaths, with all-cause mortality 67% higher than expected (observed-to-expected mortality rate: 1.67; 95% CI: 1.38–2.00). Mortality peaked the week of August 19, with a 367% increase (67 excess deaths: 3.67; 2.65–5.96). Non-medical deaths increased from 68 to 80%.ConclusionThe Lāhainā wildfire caused substantial excess mortality, likely making wildfires a leading cause of death in Maui County during this period. Findings highlight the need for improved disaster preparedness. Policy Implications. Rebuilding must incorporate Native Hawaiian ecological knowledge. Policies should focus on restoring Indigenous wetlands, removing flammable invasive grasses, and ensuring environmental justice for Native Hawaiians.